Grazing Vertebrates Promote Invasive Swamp Stonecrop (Crassula helmsii) Abundance. (June 2015) - Dean, Clare E.; Day, John; Gozlan, Rodolphe E.; Diaz, Anita
Abstract : The macrophyte swamp stonecrop has invaded a wide range of wetland habitats across Europe. An experiment was conducted within an invaded fen habitat, which tested whether the presence of grazing disturbance affected the relative abundance of swamp stonecrop, and whether any detected effect was suppressive or facilitative. The abundance of swamp stonecrop and co-occurring resident plants was monitored within fenced grazing exclosures and in adjacent unfenced plots. Swamp stonecrop abundance was higher in the unfenced plots compared to the fenced exclosures ( t (87) = 28.974, P < 0.001), whereas the abundance of co-occurring plants was higher in the fenced exclosures compared to the unfenced plots ( t (87) = 6.264, P < 0.001). These results indicate that the presence of large vertebrates could facilitate a higher abundance of swamp stonecrop in situations where competitive resident plant species were selectively removed by these grazing animals.